Effect of Enzymatic Hydrolysis on the Zinc Binding Capacity and in vitro Gastrointestinal Stability of Peptides Derived From Pumpkin (Cucurbita pepo L.) Seeds - Lu, Dan; Peng, Mengyao; Yu, Min; Jiang, Bo; Wu, Hong; Chen, Jingjing (Frontiers in Nutrition, 2021)
Zinc is a crucial micronutrient for maintaining body immune system and metabolism function. However, insufficient intake from diet may lead to zinc deficiency and impair normal body function. In addition, conventional zinc salts supplementation has the disadvantage of low bioavailability since the zinc ions may be easily chelated by dietary fiber or phytate commonly found in diets rich in plants, and form precipitates that cannot be absorbed. Therefore, the objective of the present study is to prepare pumpkin seed derived peptides and to evaluate the effect of structure and surface properties on the zinc binding behavior of the pumpkin seed protein hydrolysate (PSPH), as well as their gastrointestinal stability. Briefly, different PSPHs were prepared using enzymatic hydrolysis method with bromelain, papain, flavourzyme, alcalase, and pepsin. The particle size, zeta potential, surface hydrophobicity, degree of hydrolysis, ATR-FTIR spectra, and zinc binding capacity were determined. The representative samples were chosen to characterize the binding energy and surface morphology of PSPH-Zn. At last, the in vitro gastrointestinal stability of PSPH and PSPH-Zn were evaluated. Our results showed that peptides hydrolyzed by papain had the largest average molecular weight, smallest particle size, highest hydrophobicity, and the greatest zinc binding capacity. Zinc showed better gastrointestinal stability in PSPHs chelates than in its salt. Meanwhile, PSPH-Zn with higher zinc binding capacity showed better stability. The result of this study indicated pumpkin seed hydrolyzed by papain may be used as a potential source for zinc fortification. The findings in this study may provide important implications for developing plant-based zinc chelating peptides.